Management of unresolved hemangiomas and venous malformations by N-butyl cyanoacrylate - Roy Ashim; Majumdar Bijay; Majumdar Saswati (Indian Journal of Plastic Surgery, 2007)
Management of unresolved hemangiomas and venous malformations is a real challenging problem because of their grotesque nature and aesthetic considerations. In our study we have used percutaneous injection of N-butyl cyanoacrylate (NBCA) in such lesions to make these lesions amenable to easy excision. When the NBCA comes in contact with tissue fluid, it causes intercompartmental tissue adhesion, thus there is cessation of blood flow into the vascular malformation tissue. After few injections the whole mass forms a solid polymer, which is then excised. During excision there is remarkably minimum bleeding. In small lesions, per-operative injection just prior to surgery was also done.